ANALISIS KANDUNGAN LOGAM BERAT KADMIUM (Cd) PADA IKAN BANDENG (Channos channos) DI PERTAMBAKAN KECAMATAN PANGKAJENE - Haeriah Haeriah (Teknosains, 2018)
This research is done to know the values of precious metal cadmium (Cd) contained in milk fish (Channos channos) at Pangkajene subdistrict earthen dam. The sample analize in done by SSA. The result is gotten to show the values of precious metal cadmium (Cd) in kidney as much as 0,1070 ppm, heart 0,1002 ppm, intestines 0,0665 ppm and muscle 0,0361 ppm. The values of precious metal cadmium that get from all the sample of milk fish (Channos channos) at Pangkajene subdistrict earthen dam according WHO that still below of standardization cadmium concentration at fish namply 0,2 ppm.